PRODUCTIVITY AND EFFICIENCY OF AGRO-FOOD FIRMS IN INDIA: AN APPLICATION OF DATA ENVELOPMENT ANALYSIS AND MALMQUIST PRODUCTIVITY INDEX (International Journal of Food and Nutritional Sciences, 2022)
Given the backward and forward linkages; and export potential of agro-food firms, in this paper an attempt has been made to analyse the firm level efficiency and total factor productivity of this sector. In this context, Data Envelopment Analysis and Malmquist Productivity Index were utilized panel data spanning over twenty two years from 1994-95 to 2015-16 75 Indian agro-food firms. Broadly, study concluded that the first and second generation reforms contributed considerably to efficiency and total factor productivity of agro-food firms. Specifically, Technological change during the second generation reforms was instrumental to aise the productivity. However, global meltdown and overall fall in demand for exports lead to fall in productivity after 2008.